Immunomodulatory and growth-promoting effect of a probiotic supplemented in the feed of broiler chicks vaccinated against infectious bursal disease - S Naseem; SU Rahman; M Shafee; AA Sheikh; A Khan (Brazilian Journal of Poultry Science, 2012)
This study was designed to investigate the effects of a probiotic plus an immunomodulatory product on the growth performance, immune response and net economic returns of broiler chicks vaccinated against Infectious bursal diseases virus (IBDV). A flock of 350 day-old chicks were equally and randomly distributed in seven groups, each comprising 50 birds. A mixture of microorganisms (¹Probiotic) or Cyclophosphamide (immune suppressor) was offered through feed supplementation to different groups. The Probiotic, consisting of Lactobacillus species, Bifidobacterium, Streptococcus salivarius and Enterococcus faecium, in addition to Aspergillus oryza and Candida pintolopessii. Compared with control treatment group, the probiotic-supplemented chicks had better feed conversion ratio (FCR) (1.938 and 1.959), with significantly heavier live body weight 2141.0±34.2 and 2120.3±33.2, respectively. Similarly, their antibody titers against IBDV were significantly higher (941 and 832) on day 35. No morbidity and mortality were observed in these groups. This study suggests that a product composed of a probiotic and cyclophosphamide enhanced the growth rate as well as the immunity against infectious bursal disease virus of broilers chicks.